Mass spectrometry reveals potential of β-lactams as SARS-CoV-2 Mpro inhibitors. Issue 12 (19th January 2021) - Malla, Tika R.; Tumber, Anthony; John, Tobias; Brewitz, Lennart; Strain-Damerell, Claire; Owen, C David; Lukacik, Petra; Chan, H. T. Henry; Maheswaran, Pratheesh; Salah, Eidarus; Duarte, Fernanda; Yang, Haitao; et al.
Abstract : A high-throughput mass spectrometry based M pro assay identifies penicillin esters as new SARS-CoV-2 M pro inhibitors. Abstract : The main viral protease (M pro ) of SARS-CoV-2 is a nucleophilic cysteine hydrolase and a current target for anti-viral chemotherapy. We describe a high-throughput solid phase extraction coupled to mass spectrometry M pro assay. The results reveal some β-lactams, including penicillin esters, are active site reacting M pro inhibitors, thus highlighting the potential of acylating agents for M pro inhibition.